Molecular-Genetic Identification of Darevskia unisexualis × D. valentini Triploid Hybrids from Sympatric Populations of Armenia - Girnyk, A. E.; Vergun, A. A.; Arakelyan, M. S.; Ryskov, A. P. (Molecular genetics, microbiology and virology, 2021)
Seven putative triploid hybrid Darevskia lizards were genotyped on the basis of the Du215 microsatellite locus. The alleles at this locus were identified and sequenced in these individuals. We found that five out of seven individuals are triploid hybrids of Darevskia unisexualis × D. valentini , each containing two alleles of the D. unisexualis parthenospecies and one allele of D. valentini . The other two individuals were heterozygous at this locus and contained alleles only of the bisexual species D. valentini .